Loss of Cultural and Functional Diversity Associated With Birds Across the Urbanization Gradient in a Tropical City - Valente-Neto, Francisco; Roque, Fabio de Oliveira; Pauliquevis, Carolina Ferreira; Oliveira, Ademir Kleber Morbeck de; Provete, Diogo B.; Szabo, Judit K.; Souza, Franco Leandro (Frontiers in Ecology and Evolution, 2021)
Birds provide many ecosystem services to people, including provisioning, regulating and cultural services. People attribute multiple cultural values to ecosystems and biodiversity and the diversity of these cultural values can be considered as cultural diversity. While human-nature interactions occur more frequently in cities and urbanization negatively affects different facets of avian biodiversity, little is known about its consequence for cultural diversity. Here, we assess how the urbanization gradient in Campo Grande, a Brazilian city in the Cerrado biodiversity hotspot, affects functional and cultural diversity associated with birds and if functional and cultural diversity are congruent. We also investigate the relation between urbanization gradient with functional traits and cultural values, weighted by species abundance. We used a dataset based on bird surveyed in 61 landscapes along a gradient of impervious surface cover. To estimate functional and cultural diversity, we used indices that estimate richness and divergence of functional traits and cultural values. We found that urbanization affected functional and cultural richness negatively, while there was no effect on functional and cultural divergence. Functional and cultural richness and functional and cultural divergence were weakly, but significantly correlated. Bird species that nested on trees decreased and those that nest in artificial structures and on the ground increased along impervious surface gradient. Body size, diet, habitat, mating system, flock behavior and all cultural values (number of times the species was mentioned by football teams, music or poetry, city flags and anthems, and folklore tales) were not significantly affected by impervious surface. The negative relationship between impervious surface and bird cultural richness may indicate that people living in more urbanized areas experience nature less compared to people in less urbanized areas, which can affect their psychological well-being. In these highly urbanized areas, contact with culturally valued birds and cultural services provided by birds may also diminish. The negative relationship between functional richness and urbanization also indicated that highly urbanized areas may be losing important ecosystems services provided by birds.